Biomedical Applications of Hydrogels Handbook - Ottenbrite, Raphael M.; Park, Kinam; Okano, Teruo (Springer New York : Imprint: Springer, 2010)
Hydrogels are networks of polymer chains which can produce a colloidal gel containing over 99 per cent water. The superabsorbency and permeability of naturally occurring and synthetic hydrogels give this class of materials an amazing array of uses. These uses range from wound dressings and skin grafts to oxygen-permeable contact lenses to biodegradable delivery systems for drugs or pesticides and scaffolds for tissue engineering and regenerative medicine. Biomedical Applications of Hydrogels Handbook provides a comprehensive description of this diverse class of materials, covering both synthesis and properties and a broad range of research and commercial applications. The Handbook is divided into four sections: Stimuli-Sensitive Hydrogels, Hydrogels for Drug Delivery, Hydrogels for Tissue Engineering, and Hydrogels with  Unique Properties. Key Features: Provides comprehensive coverage of the basic science and applications of a diverse class of materials Includes both naturally occurring and synthetic hydrogels Edited and written by worldwide leaders in the field Editorial Advisory Board: Nicholas A. Peppas, Chair (The University of Texas at Austin)   Allan Hoffman (University of Washington) Emo Chiellini (University of Pisa)   Fu-Zhai Cui (Tsinghua University)   Karel Dusek (Academy of Sciences of the Czech Republic)   Jindrich Kopecek (University of Utah)   Claudio Migliaresi (University of Trento)   Yoshihito Osada (Hokkaido University)   Buddy D. Ratner (University of Washington) Nathan Ravi (Washington University in St. Louis)   Etienne Schacht (Ghent University)   Tianwei Tan (Bejing University of Chemical Technology).